ANALISIS PEMBERIAN PELATIHAN KEMANDIRIAN TERHADAP KETERAMPILAN WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KELAS IIA KENDARI - Rizky, Muhammad; Razak, Abdul; Supriadin, Nofal (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to find out about the provision of independence training for the skills of correctional inmates at the Kendari Class IIA Correctional Institution. The informants in this research were 1. Head of the Job Guidance Section, 2. Prisoners, 3. Former prisoners. The research design used in this research is qualitative research with a descriptive approach. The results of research regarding the implementation of independence training for prisoners at the Kendari Class IIa Correctional Institution can be concluded that the provision of Independence Training for the Skills of Correctional Inmates at the Kendari Class IIA Correctional Institution is felt by all prisoners, both those currently serving their sentences and those who have been released, because it has a big impact on sustainability. his life after he was released, as well as changing the mainstream of the wider community who seemed to look down on ex-convicts that ex-convicts were the trash of society.